Mass-transfer studies at rotating cylinder electrodes with turbulence promoters - Grau, Javier Mario (2011)
Mass transfer was studied at a rotating cylinder electrode with different turbulence promoters using the reduction of ferricyanide as a test reaction. Four types of turbulence promoters were examined: expanded plastic meshes, Teflon structures, a plastic woven mesh and a plastic perforated net, which were rotated together with the electrode. The best performance was obtained for the Teflon structures at low rotation speeds and for the plastic woven mesh at high rotation speeds. The effect of both the length and the number of sheets of the turbulence promoters as well as the use of static promoters were also analysed. Comparisons of mass-transfer performance of turbulence promoters are made with other three-dimensional structures. The mass-transfer enhancement factor related to a smooth rotating cylinder electrode is twice as large.